Kontribusi Penelitian Universitas terhadap Pendapatan Industri: Bukti Empiris dari Top University di Indonesia - Cliff Kohardinata; Luky Patricia Widianingsih; Alexandre Desousa Guterres (Departement of Mathematics Education, 2023)
Competition does not only occur in the business world, but universities also must compete against competition from both domestic and foreign universities. One important indicator for university ranking is industry revenue which reflects commercial value and strengthens university-industry collaboration. The purpose of this study is to obtain empirical evidence regarding the effect of teaching, research, and citations on industrial income. This study uses a multiple linear regression approach, using data from The Times Higher Education World University Ranking from 2019-2023 to get a sample of universities in Indonesia which are included in it. The results showed that teaching had no significant effect on industrial income, research had a significant positive effect on industrial income, and citations had a significant negative effect on industrial income.